Dominant twin peaks: a novel conjecture for the pathophysiologic basis of tremor frequency and fluctuation time in Parkinson’s disease - Furrukh Khan; David Novikov; Brian Dalm; Jessie Xiaoxi; Oliver Flouty; Evan Thomas (Frontiers in Neuroscience)
BackgroundWith the commercial availability of deep brain stimulation neurostimulators and sensing leads capable of recording deep brain Local Field Potentials, researchers now commonly study the spectral characteristics of Local Field Potentials recorded from the subthalamic nucleus of patients with Parkinson’s disease. Correlating subthalamic synchronized oscillatory activity with motor impairment in Parkinson’s disease patients has recently gained attention in the literature.ObjectiveBased on the deep brain recordings of a Parkinson’s disease patient our objective is to (i) Use actual measurements of the patient’s tremor to support a hypothesis that connects the features of the Local Field Potential’s beta-band spectrum (13–31 Hz), with the lower frequency (4–8 Hz) features of the patient’s tremor, such as tremor frequency and tremor fluctuation time and (ii) Justify the hypothesis through theoretical reasoning based on communication theory in Electrical Engineering.MethodsTremor characteristics (i.e., tremor frequency and tremor fluctuation time) derived from limb coordinate time-series were obtained from a video of the patient by using Google’s MediaPipe Artificial Intelligence Framework. Spectra of the deep brain recordings and measured tremor time-series were analyzed using the Fast Fourier Transform. Burst trains in the deep brain signals and tremor bursts in the measured tremor signal were investigated by using Continuous Wave Transform scalograms.ResultsSupport for the hypothesis is provided by a close agreement between the measured results of the tremor (from a patient’s video) and the predictions of the hypothesis based on the Local Filed Potential deep brain spectrum. We show that the defining features in the scalogram obtained from the deep brain signal are directly related to the features in the scalogram of the measured tremor. We provide a theoretical justification of the hypothesis by relating features of the deep brain beta-bursts, seen in the Local Field Potential scalogram, to a pair of beta-band dominant peaks found in the spectrum of the deep brain signal by leveraging the phenomena of “beating” (amplitude modulation) from communications theory.ConclusionWe conclude that tremor properties of a Parkinson’s disease patient, like tremor frequency and tremor fluctuation duration, can be obtained from the patient’s subthalamic nucleus beta-band spectrum.